Genome-wide Analysis of MYB Gene Family in Potato Provides Insights into Tissue-specific Regulation of Anthocyanin Biosynthesis - Li, Y.; Liang, J.; Zeng, X.; Guo, H.; Luo, Y.; Kear, P.; Zhang, S.; Zhu, G. (Elsevier, 2021)
The MYB transcription factor is one of the largest gene families in plants, playing an important role in regulating plant growth, development, response to stress, senescence, and especially the anthocyanin biosynthesis. In this study, A total of 217 MYB genes, including 90 1R-MYBs, 124 R2R3-MYBs, and 3 R1R2R3-MYBs have been identified from the potato genome. The 1R-MYB and R2R3-MYB family members could be divided into 20 and 35 subgroups respectively. Analysis of gene structure and protein motifs revealed that members within the same subgroup presented similar exon/intron and motif organization, further supporting the results of phylogenetic analysis. Potato is an ideal plant to reveal the tissue-specific anthocyanins biosynthesis regulated by MYB, as the anthocyanins could be accumulated in different tissues, showing colorful phenotypes. Five pairs of colored and colorless tissues, stigma, petal, stem, leaf, and tuber flesh, were applied to the transcriptomic analysis. A total of 70 MYB genes were found to be differentially expressed between colored and colorless tissues, and these differentially expressed genes were suspected to regulate the biosynthesis of anthocyanin of different tissues. Co-expression analysis identified numerous potential interactive regulators of anthocyanins biosynthesis, involving 39 MYBs, 24 bHLHs, 2 WD-repeats, and 29 biosynthesis genes. Genome-wide association study (GWAS) of tuber flesh color revealed a major signal at the end of Chromosome 10, which was co-localized with reported I gene (StMYB88), controlling tuber peel color. Analyses of DEGs (Differentially Expression Genes) revealed that both StMYB88 and StMYB89 were closely related to regulating anthocyanin biosynthesis of tuber flesh. This work offers a comprehensive overview of the MYB family in potato and will lay a foundation for the functional validation of these genes in the tissue-specific regulation of anthocyanin biosynthesis.